A highly stable inorganic sulfide electrolyte and its preparation method and application
By forming a V-rich layer on the surface of the sulfide solid electrolyte, the problem of its reaction with water and insufficient stability is solved, and high stability and excellent circulation performance are achieved, and it is suitable for all-solid lithium secondary batteries.
Patent Information
- Application Number
- CN202410136702.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-01-31
AI Technical Summary
The solid electrolyte of sulfide reacts with water to form toxic hydrogen sulfide gas. The conditions for use are harsh, which limits its large-scale use. The prior art cannot effectively solve the problem of close contact between the organic cladding and the sulfide core, and there is a risk of shell falling off.
The sulfide solid electrolyte is treated with V-containing compounds, and a V-rich layer is formed on its surface to block/absorb moisture, improve the stability with the oxide positive electrode, and enhance the cycling performance of the composite positive electrode.
It realizes a highly stable inorganic sulfide electrolyte, improves the stability to water and the stability of ultra-high nickel oxide positive electrode, enhances the circulation performance of all-solid lithium secondary batteries, and is suitable for various solid electrolyte materials containing S elements.
Smart Images

Figure BDA0004691511700000111 
Figure HDA0004691511710000011 
Figure HDA0004691511710000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a highly stable inorganic sulfide electrolyte and a preparation method and application thereof. Background Art
[0002] With the further development of the new energy industry, new energy vehicles have put forward higher requirements for the safety and energy density of power batteries. The scientific research community and the industry have reached a consensus that all-solid-state batteries that use solid electrolytes to replace traditional liquid electrolytes are one of the most promising technical solutions. Among the many solid electrolyte materials, sulfide solid electrolyte materials such as argyrodite have high ionic conductivity close to that of liquid electrolytes, and have the advantages of easy availability of raw materials, low Young's modulus, and close combination with active substances. Therefore, all-solid batteries using sulfide solid electrolytes are expected to be the first to be put into practical use.
[0003] The main disadvantage of sulfide solid electrolytes is that they react with water to generate toxic hydrogen sulfide gas, so the use conditions are harsh, which limits their large-scale use and has become a major technical problem restricting the development of this field. To solve this problem, some documents and inventions have proposed element doping schemes, such as ACS Appl. Mater. Interfaces 2022, 14, 4179-4185, ACSSustainable Chem. Eng. 2020, 8, 3321-3327, CN110085908A, CN113097560A, etc. The limitation of this method is that the doping elements cause the decrease of the ion conductivity of the electrolyte material, and the introduction of high-value (such as Ge) or highly toxic (such as As) doping elements causes an increase in material costs or damage to the health of operators. Inventions CN115377481A and CN111129579A disclose organic-inorganic composite solid electrolytes. The organic coating layer can improve the wet air stability of the core sulfide electrolyte. However, there is still the problem that the surface polymer itself is an unstable organic substance and there is a risk of fire when heated. Invention patent CN112018458B reports an aqueous sulfide-polymer composite solid electrolyte, which is still an organic-inorganic composite in nature, and the template method cannot provide a powdered electrolyte material with wider applicability according to the use requirements of all-solid-state batteries.
[0004] Finally, the above technical solutions cannot solve the problem of close contact between the organic coating layer and the sulfide core, and there is a risk of shell shedding. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a highly stable inorganic sulfide electrolyte and a preparation method and application thereof.
[0006] The present invention uses a V-containing compound to treat the sulfide solid electrolyte, and forms a V-rich layer on the surface of the sulfide solid electrolyte, which can solve the above technical difficulties. The V-rich surface layer plays a role in blocking / absorbing moisture. The V-rich surface layer can also improve the stability between the sulfide solid electrolyte and the oxide positive electrode, and improve the cycle performance of the composite positive electrode.
[0007] Specifically, the highly stable inorganic sulfide electrolyte provided in the first aspect of the present invention has a surface rich in V, and the thickness of the V-rich layer is 10 to 20 nm; the mass fraction of V in the V-rich layer of the inorganic sulfide electrolyte is 10% to 60%, and the inorganic sulfide electrolyte also contains P and / or halogen.
[0008] More preferably, the thickness of the V-rich layer is 12 to 18 nm, for example, 12 nm, 13 nm, 15 nm, 16 nm, 17 nm, 18 nm, etc.
[0009] The present invention has found that when the mass fraction of V in the V-rich layer is between 10% and 60% and the thickness is between 12 and 18 nm, the comprehensive effect of the inorganic sulfide electrolyte is optimal. If the V content is too low or the thickness is too small, the stability improvement is not obvious, while if the V content is too high or the thickness is too large, the ion conductivity of the sulfide is affected.
[0010] In the present invention, the halogen includes F, Cl, Br, and I.
[0011] Preferably, the V-rich layer further contains Li and / or O; preferably, in the V-rich layer, the mass fraction of Li element is 0-30%, and the mass fraction of O element is 0-60%.
[0012] In the present invention, the V-rich layer contains at least Li and / or O, wherein the mass fraction of Li is 0-30%, and the mass fraction of O is 0-60%; more preferably, the mass fraction of Li is 1%-20%, and the mass fraction of O is 10%-55%. The presence of these elements can synergize with V to further improve stability.
[0013] The second aspect of the present invention provides a method for preparing a highly stable inorganic sulfide electrolyte, comprising: mixing an inorganic sulfide electrolyte material and a V-containing compound, and then performing a heat treatment to obtain the highly stable inorganic sulfide electrolyte.
[0014] The inorganic sulfide electrolyte material used in the present invention is a prepared inorganic sulfide electrolyte material or a commercial inorganic sulfide electrolyte material.
[0015] Preferably, the inorganic sulfide solid electrolyte material is selected from one or more of the chemical formulas represented by formula (I), formula (II) and formula (III):
[0016] xLi2S-(100-x)P2S5-yM m X n (Ⅰ)
[0017] In formula (I), 70≤x≤80, 0≤y<100, 0≤m<4, 0≤n<6; M is selected from one or more of Ge, Si, Sn, Sb, Al, and X is selected from one or more of Cl, Br, I;
[0018] Li 10±i N'P2Y 12 (Ⅱ)
[0019] In formula (II), 0≤i<1.0; N' is selected from one or more of Ge, Si, Sn, Sb, Al, and Y is selected from one or more of Cl, Br, I;
[0020] Li 6±a P 1-b M' b S 5±a-c X' d (III)
[0021] In formula (III), 0≤a<1.0, 0≤b<1.0, 0≤c<1.0, 0.6≤d≤2.0; M' is selected from one or more of Ge, Si, Sn, Sb, Al, and X' is selected from one or more of Cl, Br, I.
[0022] Preferably, the inorganic sulfide electrolyte material is a combination of one or more forms of amorphous, glassy and crystalline states; further preferably, the inorganic sulfide electrolyte material is an argyrodite-type crystalline state.
[0023] Preferably, the V-containing compound is selected from one or more of vanadium oxides, vanadates, pyrovanadates, metavanadates, and carbonate vanadates.
[0024] Preferably, the V-containing compound includes VO, V2O3, VO2, V2O5, V6O 13 , Li3VO4, FeVO4, SiV2O7, Sn(VO3)4, LiV2BO5, LiV3O8, NH4VO3, NH4V3O8, Li3(VO4)(CO3), (NH4)3(VO4)(CO3), (NH4)6V 10 O 28 One or more of .
[0025] In the present invention, the amount of the V-containing compound added is determined by calculation based on the mass content of the V element in the V-rich layer of the inorganic sulfide electrolyte.
[0026] Preferably, the heat treatment temperature is 350-800°C and the heat treatment time is 5-18 hours. In the present invention, when the sintering temperature is too high or too low, the ion conductivity and retention rate of the sulfide will be affected.
[0027] More preferably, the heat treatment temperature is 430-670°C, the heat treatment time is 6-8h, and the heat treatment is heated at a rate of 2-5°C / min. Under the above preferred heat treatment conditions, the effect will be better improved.
[0028] A third aspect of the present invention provides use of any of the above-mentioned highly stable inorganic sulfide electrolytes or a highly stable inorganic sulfide electrolyte prepared by any of the above-mentioned methods for preparing a highly stable inorganic sulfide electrolyte in preparing an all-solid-state lithium secondary battery.
[0029] A fourth aspect of the present invention provides an all-solid-state lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the solid electrolyte layer adopts any of the above-mentioned highly stable inorganic sulfide electrolytes, or a highly stable inorganic sulfide electrolyte prepared by any of the above-mentioned methods for preparing the highly stable inorganic sulfide electrolyte.
[0030] The beneficial effects of the present invention are at least:
[0031] 1) The present invention has a wide range of applications and can be used for various solid electrolyte materials containing S elements, and is not limited to the crystal form of sulfide electrolytes. It is suitable for the preparation process of sulfide electrolytes and is also suitable for further processing of commercially purchased sulfide electrolyte materials. The preparation method is simple, efficient and low-cost.
[0032] 2) The present invention can not only obtain a water (humid air) stable sulfide solid electrolyte, but also simultaneously improve the stability of the ultra-high nickel oxide positive electrode, which is expected to rapidly promote the large-scale application of sulfide solid electrolytes in all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. It is obvious that the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a SEM image of the solid electrolyte material obtained in Example 1 of the present invention;
[0035] Figure 2 XRD diffraction patterns of the solid electrolyte materials obtained in Example 1 and Comparative Example 1 of the present invention;
[0036] Figure 3 The solid electrolyte material obtained in Example 1 and Comparative Example 1 of the present invention is LiNi 0.90 Co 0.05 Mn 0.05 Cycling curve of the composite positive electrode prepared with O2 ternary material. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] If the specific technology or conditions are not specified in the embodiments of the present invention, the technology or conditions described in the literature in this field or the product instructions are used, and the technology or conditions include relevant preparation and testing. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market.
[0039] In the embodiment of the present invention, Li3(VO4)(CO3), V2O5, Li3VO4, FeVO4, (NH4)6V 10 O 28 Reagents and raw materials not specified are all commercially available products purchased from reagent companies.
[0040] In the embodiment of the present invention, the sulfide solid electrolyte material is prepared as follows: In a glove box, press Li 5.5 PS 4.5 Cl 1.5 Weigh Li2S, P2S5, and LiCl according to the proportion of elements in the mixture. Place the above raw materials in a 50ml zirconium oxide ball mill and add 50g of 5mm diameter zirconium oxide balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 540°C at a rate of 3°C / min and keeping warm for 12h. After sintering, cool to 50°C to obtain the sulfide solid electrolyte material (Li 5.5 PS 4.5 Cl 1.5 ), the sulfide electrolyte material is in a argyrodite-type crystalline state.
[0041] This embodiment is only used to illustrate one of the conventional preparation methods of sulfide solid electrolytes, and is not used to limit the sulfide solid electrolyte materials used in the present invention. The sulfide solid electrolyte materials used in the present invention can be obtained in any manner.
[0042] Example 1
[0043] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5 Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of Li3(VO4)(CO3) added as 0.069g based on the V content in the V-rich layer of 15%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 430°C at a rate of 3°C / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0044] The scanning electron microscope and XRD diffraction analysis results of the highly stable inorganic sulfide solid electrolyte provided in this embodiment are as follows: Figure 1 and Figure 2 As shown, after material testing and analysis, the particle diameter is 1000nm, the thickness of the V-rich layer is 12nm, the mass fraction of V in the V-rich layer is 15.0%, the mass fraction of Li in the V-rich layer is 12.2%, the mass fraction of O is 33.0%, and the remaining components are 39.8%.
[0045] This embodiment is only used to illustrate one of the conventional mixing methods of sulfide solid electrolyte and V-containing compound, and is not used to limit the mixing method used in the present invention. The sulfide solid electrolyte material used in the present invention and the V-containing compound can be mixed in any manner, including but not limited to various dry and wet mixing methods.
[0046] Example 2
[0047] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of Li3(VO4)(CO3) added as 0.14g based on the V content in the V-rich layer of 25.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 430°C at a rate of 3°C / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0048] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 15 nm, a mass fraction of V in the V-rich layer of 25.0%, a mass fraction of Li in the V-rich layer of 10.8%, a mass fraction of O of 55.0%, and the remaining components of 9.2%.
[0049] Example 3
[0050] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5 Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of V2O5 added to be 0.18g based on the V content in the V-rich layer of 56.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 670°C at a rate of 3°C / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0051] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 18 nm, a mass fraction of V in the V-rich layer of 56.0%, a mass fraction of O in the V-rich layer of 44.0%, and the remaining components of 0%, according to material testing and analysis.
[0052] Example 4
[0053] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of V2O5 added as 0.054g based on the V content in the V-rich layer of 20.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 670℃ at a rate of 3℃ / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0054] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 15 nm, a mass fraction of V in the V-rich layer of 20.0%, a mass fraction of Li in the V-rich layer of 9.2%, a mass fraction of O of 15.7%, and the remaining components of 55.1%.
[0055] Example 5
[0056] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5 Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of Li3VO4 added as 0.080g based on the V content in the V-rich layer of 20.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 580℃ at a rate of 3℃ / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0057] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 15 nm, a mass fraction of V in the V-rich layer of 20.0%, a mass fraction of Li in the V-rich layer of 14.9%, a mass fraction of O of 25.1%, and the remaining components of 40.0%.
[0058] Example 6
[0059] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the FeVO4 addition amount to 0.098g based on the V content in the V-rich layer of 20.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 600℃ at a rate of 3℃ / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material.
[0060] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 16 nm, a mass fraction of V in the V-rich layer of 20.0%, a mass fraction of Li in the V-rich layer of 4.7%, a mass fraction of O of 25.1%, and the remaining components of 50.2%.
[0061] Example 7
[0062] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5 Surface treatment: Weigh 10g of sulfide solid electrolyte material and calculate (NH4)6V based on the V content in the V-rich layer being 20.0% 10 O 28 The addition amount is 0.067g. The two raw materials are placed in a 50ml zirconium oxide ball mill jar, and 50g of 5mm diameter zirconium oxide balls are added. Place the sealed ball mill jar on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 550℃ at a rate of 3℃ / min and keeping warm for 8h. After sintering is completed, cool to room temperature to obtain the target solid electrolyte material. The thickness of its V-rich layer is 16nm.
[0063] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 16 nm, a mass fraction of V in the V-rich layer of 20.0%, a mass fraction of Li in the V-rich layer of 8.3%, a mass fraction of O of 17.6%, and the remaining components of 54.1%.
[0064] Example 8
[0065] The sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5Surface treatment: Weigh 10g of sulfide solid electrolyte material, calculate the amount of LiV2BO5 added as 0.035g based on the V content in the V-rich layer of 15.0%, place the two raw materials in a 50ml zirconia ball mill, and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by program temperature rise, rising from room temperature to 360°C at a rate of 3°C / min and keeping warm for 8h. After sintering, cool down to room temperature to obtain the target solid electrolyte material. The thickness of its V-rich layer is 12nm.
[0066] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 12 nm, a mass fraction of V in the V-rich layer of 15.0%, a mass fraction of Li in the V-rich layer of 11.1%, a mass fraction of O of 11.8%, and the remaining components of 62.1%.
[0067] Example 9
[0068] The same method as in Example 1 was used for preparation, except that the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 Replaced with Li7PS6 (the ionic conductivity of the bare sample without surface treatment is 0.27 mS / cm).
[0069] The highly stable inorganic sulfide solid electrolyte provided in this embodiment has a particle diameter of 1000 nm, a thickness of the V-rich layer of 12 nm, a mass fraction of V in the V-rich layer of 15.0%, a mass fraction of Li in the V-rich layer of 13.7%, a mass fraction of O of 33.0%, and the remaining components of 38.3%.
[0070] Comparative Example 1
[0071] The sulfide solid electrolyte material used is the same as that in Example 1, except that no surface treatment is performed.
[0072] Comparative Example 2
[0073] The preparation was carried out in the same manner as in Example 1, except that the sintering temperature was 330°C.
[0074] Comparative Example 3
[0075] The preparation was carried out in the same manner as in Example 1, except that the thickness of the V-rich layer was 25 nm.
[0076] Comparative Example 4
[0077] The preparation was carried out in the same manner as in Example 1, except that the V content was 65%.
[0078] Experimental Example 1
[0079] Ion conductivity test
[0080] Weigh 150 mg of electrolyte material, place it in a mold with an inner diameter of 10 mm, and apply 300 MPa pressure for 1 min to press it into a sheet. Then add 10 mg of carbon nanotubes on both sides of the electrolyte sheet, put it into the mold again, and apply 300 MPa pressure for 30 seconds. Place the mold in the mold battery shell, tighten the screws everywhere to ensure a tight seal. Use an electrochemical workstation to perform ion conductivity testing using electrochemical impedance spectroscopy.
[0081] Wet air stability test of solid electrolyte materials
[0082] The solid electrolytes obtained in Examples 1 to 8 and Comparative Examples 1 to 5 were subjected to a wet air stability test. In a glove box, 300 mg of the solid electrolyte material was weighed and placed in a 5 ml open glass bottle. The glass bottle was then placed in a reaction box with a specific humidity air flow and allowed to stand at room temperature. The relative humidity of the wet air was 10% and the air flow rate was 100 ml / min. After 24 hours, samples were taken and ion conductivity tests were performed.
[0083] Figure 1 This is a SEM image of the surface of the solid electrolyte material obtained in Example 1. Figure 2 The XRD diffraction patterns of the solid electrolyte materials obtained in Example 1 and Comparative Example 1 are shown. Figure 3 The solid electrolyte material obtained in Example 1 and Comparative Example 1 is LiNi 0.90 Co 0.05 Mn 0.05 Cycle curve of the composite positive electrode prepared by O2 ternary material. Table 1 is a summary table of data of Examples 1 to 8 and Comparative Examples 1 to 5.
[0084] Table 1 Data summary of Examples 1 to 8 and Comparative Examples 1 to 5
[0085]
[0086] It can be found from Table 1 that the sulfide solid electrolyte containing a V layer on the surface of the present invention effectively avoids a significant decrease in ion conductance compared with the comparative example, and in particular, the stability of the embodiment of the present invention is also greatly improved. When the V content, thickness or preparation temperature of the V-containing layer is not as required by the present invention, the ion conductance decreases significantly, and although its stability is slightly improved compared with the untreated sulfide solid electrolyte material (Comparative Example 1), the effect is very limited.
[0087] Experimental Example 2
[0088] The sulfide solid electrolyte containing a V layer on the surface of Example 1 and the sulfide solid electrolyte without a V layer on the surface of Comparative Example 1 were used as the solid electrolyte layer, respectively. 0.90 Co 0.05 Mn 0.05 The mixture of O2 ultra-high nickel oxide positive electrode and Example 1 or Comparative Example 1 is used as the positive electrode layer, and Li-In alloy is used as the negative electrode layer to assemble an all-solid-state lithium secondary battery.
[0089] The charge and discharge cycle test was carried out with a charge and discharge current of 0.1C and a voltage range of 2.5-4.3V (vs. Li / Li + ), the temperature is room temperature (25°C).
[0090] The results show that the mold battery using the sulfide solid electrolyte of the present invention shows a more excellent cycle performance ( Figure 3 ). Moreover, the sulfide solid electrolyte material obtained by the present invention has high stability for the ultra-high nickel oxide positive electrode.
[0091] The material composition of the invention is simple, the raw materials are easily available, the preparation method is simple, the production cost is low, and the invention has good wet air stability, high lithium ion conductivity, and high stability to the ultra-high nickel oxide positive electrode. The invention can solve the practical application problem of inorganic sulfide electrolyte as a high-performance all-solid-state lithium secondary battery electrolyte.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a highly stable inorganic sulfide electrolyte, characterized in that: include: The inorganic sulfide electrolyte material and the V-containing compound are mixed and then heat-treated to obtain a highly stable inorganic sulfide electrolyte; The surface of the inorganic sulfide electrolyte is V-rich, and the thickness of the V-rich layer is 12 to 18 nm; the V-rich layer also contains Li and O; the mass fraction of V in the V-rich layer of the inorganic sulfide electrolyte is 10% to 60%; the inorganic sulfide electrolyte also contains P and / or halogen; The heat treatment temperature is 430-670°C, and the heat treatment is heated at a rate of 2-5°C / min; The inorganic sulfide solid electrolyte material is selected from the chemical formula (III) Li 6±a P 1-b M' b S 5±a-c X' d (Ⅲ) In formula (III), 0≤a<1.0, 0≤b<1.0, 0≤c<1.0, 0.6≤d≤2.0; M' is selected from one or more of Ge, Si, Sn, Sb, Al, and X' is selected from one or more of Cl, Br, I; The V-containing compound is selected from Li3VO4, FeVO4, SiV2O7, Sn(VO3)4, LiV2BO5, LiV3O8, NH4VO3, NH4V3O8, Li3(VO4)(CO3), (NH4)3(VO4)(CO3), (NH4)6V 10 O 28 One or more of .
2. The method for preparing a highly stable inorganic sulfide electrolyte according to claim 1, characterized in that: In the V-rich layer, the mass fraction of Li element is 1% to 20%, and the mass fraction of O element is 10% to 55%.
3. The method for preparing a highly stable inorganic sulfide electrolyte according to claim 1, characterized in that: The inorganic sulfide electrolyte material is a combination of one or more forms of an amorphous state, a glassy state and a crystalline state.
4. The method for preparing a highly stable inorganic sulfide electrolyte according to claim 3, characterized in that: The inorganic sulfide electrolyte material is in an argyrodite-type crystalline state.
5. The method for preparing a highly stable inorganic sulfide electrolyte according to claim 1, characterized in that: The heat treatment time is 5 to 18 hours.
6. Use of the highly stable inorganic sulfide electrolyte prepared by the method for preparing the highly stable inorganic sulfide electrolyte according to any one of claims 1 to 5 in preparing an all-solid-state lithium secondary battery.
7. An all-solid-state lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, characterized in that: The solid electrolyte layer is a highly stable inorganic sulfide electrolyte prepared by the method for preparing a highly stable inorganic sulfide electrolyte according to any one of claims 1 to 5.
Citation Information
Patent Citations
Sulfide solid electrolyte material, preparation method thereof and solid-state battery
CN111129579A
Sulfide-polymer composite solid electrolyte, its preparation method and application
CN112018458B
Organic-inorganic composite solid electrolyte, preparation method thereof and lithium ion solid-state battery
CN115377481A
A sulfide solid electrolyte and its preparation method
CN114933331A
High-temperature-resistant sulfide electrolyte with core-shell structure
CN115911430A